T-helper cells flexibility: the possibility of reprogramming T cells fate - Khantakova, Julia N.; Sennikov, Sergey V. (Frontiers in Immunology, 2023)
Various disciplines cooperate to find novel approaches to cure impaired body functions by repairing, replacing, or regenerating cells, tissues, or organs. The possibility that a stable differentiated cell can reprogram itself opens the door to new therapeutic strategies against a multitude of diseases caused by the loss or dysfunction of essential, irreparable, and specific cells. One approach to cell therapy is to induce reprogramming of adult cells into other functionally active cells. Understanding the factors that cause or contribute to T cell plasticity is not only of clinical importance but also expands the knowledge of the factors that induce cells to differentiate and improves the understanding of normal developmental biology. The present review focuses on the advances in the conversion of peripheral CD4+ T cells, the conditions of their reprogramming, and the methods proposed to control such cell differentiation.